2016
DOI: 10.1371/currents.hd.cba6ea74972cf8412a73ce52eb018c1e
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Association of Physical Activity with Brain Volume, Behavior, and Day-to-day Functioning? A Cross Sectional Design in Prodromal and Early Huntington Disease

Abstract: Background: Huntington disease (HD) is a genetic neurodegenerative disease leading to progressive motor, cognitive, and behavioral decline. Subtle changes in these domains are detectable up to 15 years before a definitive motor diagnosis is made. This period, called prodromal HD, provides an opportunity to examine lifestyle behaviors that may impact disease progression. Theoretical Framework: Physical activity relates to decreased rates of brain atrophy and improved cognitive and day-to-day functioning in Alzh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 78 publications
3
15
1
Order By: Relevance
“…approximately three points higher than controls. 15,16 In our retrospective cohort, we found that there was a statistically significant difference in WHODAS scores between women with and without SMM. 7 However, there are still many gaps in our understanding of such results, as there is no baseline score or threshold to determine the clinical significance of these findings.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…approximately three points higher than controls. 15,16 In our retrospective cohort, we found that there was a statistically significant difference in WHODAS scores between women with and without SMM. 7 However, there are still many gaps in our understanding of such results, as there is no baseline score or threshold to determine the clinical significance of these findings.…”
Section: Discussionmentioning
confidence: 61%
“…Other instruments have been used to assess specific conditions such as depression, psychiatric morbidity, and anxiety . WHODAS scores among other groups, such as patients with Huntington's disease or dementia, showed that affected individuals have higher WHODAS‐36 scores, approximately three points higher than controls …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have focused on both resistance and endurance exercise training modalities, based on the suggestion that both could be of help in HD patients. All the results showed a significant increase in grey matter volume and significant improvements in verbal learning and memory, after long-training exercise [243,244,245,246,247,248].…”
Section: A Few Examples Of Exercise Effects On Neurodegeneration: mentioning
confidence: 99%
“…Perhaps this result is associated with a greater level of physical activity of people living in Polish rural areas, the possibility of free mobility and the need to perform various physical tasks in their household. Wallace et al found that a higher level of physical activity positively correlates with lower cognitive and motor deficits, improving cognitive and daily functions and probably also motor functions in people in the prodromal and early stages [ 41 ]. Trembath et al observed that an active lifestyle and environmental factors preventing passivity contribute to the later onset of HD symptoms and can have a positive effect on the course of the disease [ 42 ].…”
Section: Discussionmentioning
confidence: 99%